Epidemiology of COVID-19 and public health restrictions during the first wave of the pandemic in Ireland in 2020. (5th March 2021) - Conway, Robert; Kelly, David M; Mullane, Paul; Ni Bhuachalla, Cliodhna; O'Connor, Lois; Buckley, Claire; Kearney, Patricia M; Doyle, Sarah
Abstract: Background: We describe the epidemiological trends and report and review the public health restrictions implemented during the first wave of the COVID-19 pandemic in Ireland. Methods: The study reviewed confirmed cases of COVID-19 notified from 1 March to 18 July 2020. Data were obtained from the national COVID-19 Data Hub, the National Health Protection Surveillance Centre, the National Contact Management Programme and the European Centre for Disease Prevention and Control. Results: A total of 25 617 cases were notified during the study period. Weekly cases and deaths peaked in mid-April 2020 at 5701 and 316, respectively. Mean number of close contacts per case was lowest at 0.7 in April, rising to 6.6 by July. Outbreak settings shifted from travel and workplace in March, to healthcare in April. Restrictions implemented on 12 March extended to full lockdown on 27 March. Phased relaxation of restrictions commenced 18 May. Effective suppression of community transmission of COVID-19 was achieved by June 2020. Conclusion: Lockdown is a crude population-level restriction effective in controlling COVID-19. Phased relaxation of restrictions in Ireland, however, led to an immediate increase in mean number of contacts per case, which facilitates viral transmission unless individual-level restrictions are adhered to. This demonstrates a limitation of lockdown as a long-term mechanism of pandemic control.